If you don't go, don't hinder me : the African American sacred song tradition - Reagon, Bernice Johnson, 1942- (Abraham Lincoln lecture series., 2001)
Based on both archival and field research, these four essays describe the role of sacred songs in the history of African American culture and in the biographical experiences of the author--an African American woman, a cultural activist, and a composer. Essays center on specific genres, including the twentieth century gospel, the African American Congregational song tradition, spirituals, and freedom songs.